Six New Cases of a Caterpillar-Induced Bleeding Syndrome - Arocha-Piñango, C L; de Bosch, N B; Torres, A; Goldstein, C; Nouel, A; Argüello, A; Carvajal, Z; Guerrero, B; Ojeda, A; Rodriguez, A; Rodriguez, S (Thrombosis and Haemostasis, 1992)
We describe six new cases of a hemorrhagic diathesis induced by contact with Lonomia achelous caterpillars. Onset of clinical bleeding varied between a few hours and 10 days post-exposure. Laboratory coagulation tests showed prolonged PT, PTT and ThT; normal platelets and a marked decrease of fibrinogen, factor V, plasminogen and factor XIII (including its subunits A and S). Factors VII, II and alfa 2 anti-plasmin were variably affected. In addition, activation of the fibrinolytic system and the generation of a procoagulant effect could also be demonstrated. Two cases developed severe hemorrhagic diathesis and one of them died of a cerebral hemorrhage. Different aspects of this rare syndrome are discussed in relation to its complex physiopathology and the variability observed in all clinical and laboratory manifestations. Therapeutic recommendations and some possible hazards following replacement transfusions are also considered.